A strength degradation model of PBL shear connectors under fatigue load. (February 2023) - Chen, Yang; Ning, Jian; Ren, Chong; Yang, Yong
Abstract: Perfobond rib shear connectors (PBL shear connectors) have been widely used in steel and reinforced concrete composite bridge. To investigate the degeneration law of the bearing capacity of PBL shear connectors after a number of fatigue loading times, both static test on one specimen and fatigue test on six specimens were performed. The failure mode, ultimate bearing capacity and load-slippage curves were emphatically focused in static test, while residual performances, including the residual strength, residual slip and shear stiffness of PBL shear connectors after a certain number of fatigue loading were also studied. Furthermore, influence of number of cycles on the residual strength and residual slip of PBL shear connector specimen within the lifetime was analyzed. Test results showed that residual strength of PBL connector decreased nonlinearly with increasing loading times, and residual slip development showed a three phrase trend of "fast, slow and then fast", but the shear stiffness was basically constant during whole loading process. Based on the residual strength theory and elastic foundation theory, residual static bearing capacity of PBL shear connectors after a number of fatigue loading times was proposed. By comparison, it was found that the residual shear bearing capacity determined by proposed model agreed well with the experimental results, which would have a great significance to guarantee the safety of a structure and prevent secondary damages to a composite bridge during the service period.